Age- and weight group-specific weight gain patterns in children and adolescents during the 15 years before and during the COVID-19 pandemic - Vogel, Mandy; Geserick, Mandy; Gausche, Ruth; Beger, Christoph; Poulain, Tanja; Meigen, Christof; Körner, Antje; Keller, Eberhard; Kiess, Wieland; Pfäffle, Roland (International Journal of Obesity, 2022)
There is a concern that measures aiming to limit a further spread of COVID-19, e.g., school closures and social distancing, cause an aggravation of the childhood obesity epidemic. Therefore, we compared BMI trends during the 15 years before and during the COVID-19 pandemic. To assess the change in weight dynamics during the first months of COVID-19, we compared the trends of 3-month change in BMI-SDS (ΔBMI-SDS) and the proportions of children showing a high positive (HPC) or high negative (HNC) weight change between 2005 and 2019 and the respective changes from 2019 (pre-pandemic) to 2020 (after the onset of anti-pandemic measures) in more than 150,000 children (9689 during the pandemic period). The period of 3 months corresponds approximately to the first lockdown period in Germany. During the COVID-19 pandemic, we found a substantial weight gain across all weight and age groups, reflected by an increase in the 3-month change in BMI-SDS (β = 0.05, p < 0.001), an increase in the proportion of children showing HPC (OR = 1.4, p < 0.001), and a decrease in the proportion of children showing HNC (OR = 0.7, p < 0.001). Besides, we found the same trends since 2005 on a low but stable level with a yearly increase of ΔBMI-SDS by β = 0.001 (p < 0.001), the odds of HPC increased by OR = 1.01 (p < 0.001), and the odds of HNC decreased by OR = 0.99 (p < 0.001). These rather small effects accumulated to β = 0.02, OR = 1.14, and OR = 0.85 over the whole period 2005-2019. Alarmingly, both the long-term and the short-term effects were most pronounced in the obese subgroup. There are positive dynamics in different measures of weight change, indicating a positive trend in weight gain patterns, especially within the group of children with obesity. These dynamics are likely to be escalated by COVID-19-related measures. Thus, they may lead to a significant further aggravation of the childhood obesity pandemic.